Exercise therapy, patient education, and patellar taping in the treatment of adolescents with patellofemoral pain: a prospective pilot study with 6 months follow-up - Rathleff, Michael S. (Pilot Feasibility Stud, 2018)
BACKGROUND: Patellofemoral pain (PFP) is the most common knee condition among adolescents, with a prevalence of 6–7% resulting in reduced function and quality of life. Exercise therapy is recommended for treating PFP, but has only been tested in older adolescents (15–19 years). This pilot study aimed to investigate the adherence to, and clinical effects of, exercise and patient education in young adolescents (12–16 years), with PFP. METHODS: Twenty adolescents (16 females) with PFP were recruited from a population-based cohort to undergo a 3-month multimodal intervention. This comprised of a 30-min patient education and group-based exercise therapy. Exercises included supervised lower extremity strength exercises three times per week, in addition to similar home-based strength exercises. Outcomes included a 7-point global rating of change scale (ranging from “completely recovered” to “worse than ever”), the Knee injury and Osteoarthritis Outcome Score (KOOS), physical activity scale (PAS), weekly sports participation and health-related quality of life measured by European Quality of Life 5 dimensions Youth (EQ-5DY) and isometric knee and hip muscle strength. Pain was measured on a visual analogue scale (VAS), and satisfaction treatment was measured on a five-point Likert scale ranging from “highly satisfied” to “not satisfied at all”. These were collected at 3- and 6-month follow-ups. Adherence to supervised exercise was measured as session attendance, and adolescent self-reported adherence to home-based exercises. RESULTS: Adherence to the exercise therapy was poor, with adolescents participating in a median of 16 (IQR 5.5–25) out of 39 possible supervised training session. Five out of 18 adolescents had a successful outcome after both 3 and 6 months. There were no relevant changes in isometric muscle strength. CONCLUSION: This was the first study to investigate adherence to, and clinical effects of, exercise therapy and patient education in young adolescents with patellofemoral pain. Adherence to the exercise therapy was low with little to no clinical effects making a full clinical trial impractical. Future studies need to explore how an intervention can be successfully tailored to young adolescents with patellofemoral pain to obtain good adherence while improving pain and function.